PEMBELAJARAN ASPEK TATA BAHASA DALAM BUKU PELAJARAN BAHASA INDONESIA - Sintowati Rini Utami (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2017)
Some time ago language teaching was faced with the choice of whether to focus on teaching the use of language (language use) or focusing on 'language form teaching. That means there are two opinions on how language teaching should be done to improve language skills. Some approaches in language teaching in favor of language skills concepts that lead to 'communicative proficiency' recommend the importance of understanding the form and grammar words to facilitate student communication skills. Grammar dimensions are linked to functions as a means of good language use. The rules or rules contained in the language will guide people to the use of language that is not only good but also true. Various perspectives that have been mentioned previously reinforce the conclusion that the learning of the word form and the rules or the rules of language contribute to the functioning of Bahasa Indonesia lessons. For that reason, in the development of Indonesian language teaching materials, we also incorporate the aspects of linguistic form and language rules. To formulate the grammatical concept we must take into account and place it appropriately both in the language structure and in the use of communication. The grammar formulas in the language used include three levels of subscript, syntactic (sentential), and suprasentential level. Subsentential is how a word is formed and functioned in a sentence. Sentential is how the position of the words in the sentence, and the patterns of the words are in the form of sentences. Suprasentential is how to display the word form in an appropriate discourse. Keywords: communicative proficiency, grammatical aspects, language thinking tools, subsentential, sentential, and suprasentential Abstrak Beberapa waktu silam pengajaran bahasa dihadapkan pada pilihan apakah akan fokus mengajarkan penggunaan bahasa (language use) atau akan berfokus pada`pengajaran bentuk bahasa. Artinya ada dua pendapat tentang bagaimana pengajaran bahasa harus dilakukan untuk meningkatkan kemampuan berbahasa. Beberapa pendekatan dalam pengajaran bahasa berpihak pada konsep keterampilan berbahasa yang mengarah pada ‘communicative proficiency’ merekomendasi pentingnya pemahaman bentuk kata dan tatabahasa untuk memperlancar kemampuan berkomunikasi siswa. Dimensi tata bahasa dihubungkan dengan fungsi sebagai sarana pemakaian bahasa yang baik. Aturan atau kaidah yang terdapat dalam bahasa akan menuntun orang menghasilkan pemakaian bahasa yang tidak saja baik tetapi juga benar. Berbagai sudut pandang yang telah dikemukakan sebelumnya memperkuat kesimpulan bahwa pembelajaran bentuk kata dan aturan atau kaidah bahasa menyumbang dalam memfungsikan pelajaran Bahasa Indonesia. Untuk alasan itulah dalam pengembangan bahan ajar bahasa Indonesia juga memasukkan aspek kebahasaan berupa bentuk kata dan aturan/kaidah bahasa.Untuk merumuskan konsep tata bahasa kita harus memperhitungkan dan menempatkan secara tepat baik dalam struktur bahasa maupun dalam penggunaan komunikasi. Rumusan tata bahasa dalam bahasa yang digunakan mencakup tiga tataran yaitu tataran morfologi (subsentential), tataran sintaksis (sentential), dan tataran wacana (suprasentential). Subsentential adalah bagaimana sebuah kata dibentuk dan difungsikan dalam kalimat. Sentential adalah bagaimana kedudukan kata kata dalam kalimat, dan pola-pola pengguanannya dalam bentuk kalimat. Suprasentential adalah bagaimana menampilkan bentuk kata dalam sebuah wacana yang sesuai. Kata kunci: communicative proficiency, aspek tata bahasa, bahasa alat berpikir, subsentential, sentential, suprasentential